Pengaruh Konseling Gizi menggunakan Kalender Menu terhadap Asupan Karbohidrat dan Kadar Gula Darah pada Penderita Diabetes Melitus Tipe II - Nashyha, Siti; Mulyani, Nunung Sri (Jurnal Akademika Baiturrahim Jambi, 2025)
Diabetes Mellitus is a degenerative disease with symptoms arising from an increase in blood sugar (glucose) levels due to lack of the hormone insulin in the body. In overcoming the prevalence of Diabetes Mellitus, nutritional counseling is needed, one of which is using menu calendar media that contains menu pictures that are practical and easy to understand. This study aims to determine the effect of nutritional counseling using a menu calendar on carbohydrate intake and levels Methods: This research is descriptive analytic with a quasi-experimental approach with a pretest- posttest design. Sampling was carried out using the Purposive Sampling technique which obtained as many as 22 samples. The study will be conducted in August 2023. Carbohydrate intake was collected using Food Recall and blood sugar levels using Accu Check. Data analysis using Dependent T-test. The average of carbohydrate intake before nutrition counseling using calendar menu in patients Diabetes Mellitus (DM) with Type II was 180.15 grams and carbohydrate intake after 160.62 grams, which means a decrease in general carbohydrate intake of 40,8 grams. The average blood sugar level before nutritional counseling using calendar menu in patients with Type II Diabetes Mellitus (DM) was 158.09 mg / dL and blood sugar levels after 109.41 mg / dL, which means a decrease in blood sugar levels in general of 48.68 mg / dL. There is an influence of counseling using Calendar Menu media on carbohydrate intake and blood sugar levels in type II Diabetes Mellitus patients at RSUD dr. Fauziah Bireuen with p values of 0.000 and 0.0001 (p<0.05).